Body Mass Index and Fat Percentage of Men’s Senior Volleyball Players from Kirtipur - Maharjan, Pradip (Mangal Research Journal, 2025)
Body composition is a key factor for performance in volleyball and helps to achieve an optimal ratio of lean-to fat mass needed for agility, power and endurance. The aim of this study was to assess the Body Mass Index (BMI) and body fat percentage (BF%) of senior men’s volleyball players in Kirtipur Municipality in terms of their general fitness profile. A descriptive research design was used, and descriptive statistics of 36 players in four wards, were performed across three thematic dimensions: general anthropometric trends, ward-level differences and association of BMI with BF%. The results revealed that many players were overweight according to BMI but their percentages of body fat were of moderate and attainable range, which means that the excess BMI was a result of higher lean muscle mass and not of overweight. The same kind of thing can also be observed from analysis of ward-wise categories. Players in Ward No. 3 possessed the greatest BMI and BF% combination, indicating worse conditioning conditions, whereas in Ward No. 10 their low BF% looked leaner and more agile. These results demonstrate the criticality of using the BF% in combination with BMI in order to determine the true level of fitness in volleyball players.